2021
DOI: 10.1073/pnas.2006786118
|View full text |Cite
|
Sign up to set email alerts
|

Mad dephosphorylation at the nuclear pore is essential for asymmetric stem cell division

Abstract: Stem cells divide asymmetrically to generate a stem cell and a differentiating daughter cell. Yet, it remains poorly understood how a stem cell and a differentiating daughter cell can receive distinct levels of niche signal and thus acquire different cell fates (self-renewal versus differentiation), despite being adjacent to each other and thus seemingly exposed to similar levels of niche signaling. In the Drosophila ovary, germline stem cells (GSCs) are maintained by short range bone morphogenetic protein (BM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Therefore, the signal may not be preferable for differentiating daughter cells for initiating differentiation program. In male and female germline stem cell system in Drosophila, a number of studies have revealed how a steep gradient of BMP response within a single cell diameter distance is established and thus contribute to asymmetric outcome of stem-cell division [23][24][25][26][27][28][29][30][31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the signal may not be preferable for differentiating daughter cells for initiating differentiation program. In male and female germline stem cell system in Drosophila, a number of studies have revealed how a steep gradient of BMP response within a single cell diameter distance is established and thus contribute to asymmetric outcome of stem-cell division [23][24][25][26][27][28][29][30][31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Signaling from the stem cell niche is believed to maintain the "stemness" of resident stem cells and the niche Dpp signal has been postulated to act as a highly localized niche signal. Using Drosophila male and female gonads, many studies have revealed how a steep gradient of BMP response is established within just one cell diameter that maintains a GSC fate (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Many of these studies postulated redundant mechanisms in which differentiating cells actively suppress downstream molecules, leaving the possibility that the diffusion of Dpp may be present (45).…”
Section: Discussionmentioning
confidence: 99%
“…Cell polarity refers to the asymmetric distribution of cytoskeleton, organelles and biomacromolecules due to the cooperation or rejection of polarity protein complexes, 3 so that different regions of the cell can perform different functions, which plays an important role in embryonic development, 4 cell differentiation, 5 cell migration, 6 asymmetric cell division (ACD) 7 and tumour development 8 . According to the distribution characteristics of polarity protein complexes and cell morphology, cell polarity can be divided into four categories: Apical‐basal polarity (ABP), 9,10 Planar cell polarity (PCP), 11,12 Front‐rear polarity (FRP) 13–15 and ACD 16–18 . ABP is the one category of cell polarity which closely relates to the differentiation and maturation of AB and the formation of enamel.…”
Section: Introductionmentioning
confidence: 99%
“… 8 According to the distribution characteristics of polarity protein complexes and cell morphology, cell polarity can be divided into four categories: Apical‐basal polarity (ABP), 9 , 10 Planar cell polarity (PCP), 11 , 12 Front‐rear polarity (FRP) 13 , 14 , 15 and ACD. 16 , 17 , 18 ABP is the one category of cell polarity which closely relates to the differentiation and maturation of AB and the formation of enamel. The AB in terminal differentiation and mature condition show a typical ABP structure, which is mainly manifested in the following aspects: the cells being high columnar and the nuclei being far away from the basement membrane and arranged in a palisade pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylated Mad (pMad) translocates into the nucleus to directly suppress bam transcription. In the pre-CBs, however, turnover of pMad is shifted towards its degradation, which leads to the de-repression of bam transcription and to differentiation [28]. Recently, the transcription factor Krüppel (Kr) has been demonstrated to be involved in the temporal regulation of bam transcription independently of the dpp signaling.…”
Section: Introductionmentioning
confidence: 99%